Statistical Response Burden of Companies: Cutting Back Obligation to Report Cannot Contribute Much to Reduction of Bureaucracy - Ingo Pfeiffer; Reiner Stäglin (Weekly Report, 2006)
The official statistics are often on the agenda when discussions about the burden of economic agents due to "bureaucracy" take place. They are often considered to be an example of unnecessary but time-consuming demand on companies by the government. A study of the Germany Institute for Economic Research commissioned by the Federal Ministry of Economics and Technology depicts that, with its 230 million Euro per year, the burden of companies due to official statistics is substantially smaller than often claimed. Other legal obligations to respond and to report, such as in personal management, take up much more time. This study, based on information from about 75,000 companies, rectifies previous substantially higher cost estimations of other institutes. A result from this finding: a quick and widely noticeable success in reducing bureaucratic burden cannot be achieved, even with a drastic cutback of surveys from Statistical Offices. Nonetheless, many companies do not complain without reasons. A small part of companies must regularly deliver time-consuming statistical responses. A more even distribution of burden should be seen to.
Keywords: 330